Part 2: Evidence Evaluation and Management of Conflicts of Interest: 2015 International Consensus on Cardiopulmonary Resuscitation and Emergency Cardiovascular Care Science With Treatment Recommendations - Morley, P.; Lang, E.; Aickin, R.; Billi, J.; Eigel, B.; Ferrer, J.; Finn, Judith; Gent, L.; Griffin, R.; Hazinski, M.; Maconochie, I.; Montgomery, W.; et al. (Lippincott Williams & Wilkins, 2015)
Introduction The international resuscitation community, under the guidance of the International Liaison Committee on Resuscitation (ILCOR), has continued its process to identify and summarize the published resuscitation science in the documents known as the ILCOR Consensus on Science with Treatment Recommendations (CoSTR). The accompanying articles represent the culmination of many years work, where a total of 250 evidence reviewers from 39 countries completed 165 systematic reviews on resuscitation related questions.